STUDY OF HEPATITIS B VIRUS INFECTION AND ITS GENOTYPES IN TRIBAL PEOPLE - Alotaibi, Amal; Khan, Johra (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was undertaken to screen the epidemiology of hepatitis B virus (HBV) in ethnically distinct, tribal dominated and of lower socioeconomic status area. Methods: Briefly, 3 ml blood was collected from 50 random liver disease cases with jaundice, receiving care at Central Hospital, N.F. Railway, Guwahati, and Guwahati Medical College, with informed consent. The patients detected with hepatitis A virus (HAV)-immunoglobulin M positive status were included and were stratified as acute viral hepatitis and fulminant hepatitis failure based on the clinical profile. HAV genotyping was studied by polymerase chain reaction-direct sequencing-phylogenetic analysis approach. Statistical analysis was performed using SPSS 13.0 software. Result: A total of 50 cases were HBV infected. HBV infection was predominant in the young and adult age group. HBV-RNA was detected in 19 cases. Conclusion: This study shows that HBV genotype D is most commonly found hepatitis in all tribes of Assam and poor sanitation and alcohol consumption are a common reason for its widespread. Keywords: Genotype, Hepatitis B virus, Liver disease, Molecular epidemiology, Phylogenetic study.